ALLOMETRIC EQUATIONS FOR ESTIMATING ABOVEGROUND BIOMASS IN PAPUA TROPICAL FOREST - Maulana, Sandhi Imam (Secretariat of Forestry Research and Development Agency, 2014)
Allometric equations can be used to estimate the biomass and carbon stock of forest. However, so far the allometric equations for commercial species in Papua tropical forest have not been appropriately developed. In this research, allometric equations are presented based on the genera of commercial species. Few equations are developed for the Intsia, Pometia, Palaquium and Vatica genera, and an equation of a mix of these genera represents commercial species. The number of trees sampled in this research was 49, with diameters (1.30 m or above buttresses) ranging from 5 to 40 cm. Destructive sampling was used to collect the samples where diameter at breast height (DBH) and wood density (WD) were used as predictors for dry weight of total above-ground biomass (TAGB). Model comparison and selection were based on the values of F-statistics, R-sq, R-sq (adj), and average deviation. Based on these statistical indicators, the most suitable model is Log(TAGB) = c + aLog(DBH). This research finding can be extrapolated for managing forests related to carbon balance. Additional explanatory variables such as commercial bole height (CBH) do not really increase the indicatorsâ goodness of fit for the equation. An alternative model to incorporate wood density must be considered for estimating the aboveground biomass for mixed genera.Â Comparing the presented equations to previously published data shows that these local species-specific and generic equations differ substantially from previously published equations and that site-specific equations must be considered to get a better estimation of biomass.